2008
DOI: 10.1177/0272989x08327113
|View full text |Cite
|
Sign up to set email alerts
|

Peer Review in Publication: Factors Associated with the Full-Length Publication of Studies Presented in Abstract Form at the Annual Meeting of the Society for Medical Decision Making

Abstract: : A significant proportion of studies presented at the SMDM meeting are not published in full length. This failure to publish is substantially higher as compared with findings from other medical and biomedical meetings. A further study is needed to explore the reasons for this low publication rate and to compare the fate of SMDM meeting abstracts to those of similar conferences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 10 publications
2
36
1
3
Order By: Relevance
“…An overall quality score (range, 0-8) was calculated with quality categorized as low (0-2 scores), moderate (3)(4)(5) and high (6)(7)(8). These scores and categorizations were only used for subsequent meta-regressions and sensitivity analyses, not any weight-assignment of data synthesis.…”
Section: Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…An overall quality score (range, 0-8) was calculated with quality categorized as low (0-2 scores), moderate (3)(4)(5) and high (6)(7)(8). These scores and categorizations were only used for subsequent meta-regressions and sensitivity analyses, not any weight-assignment of data synthesis.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…However, conference abstracts are usually difficult to locate and access, present preliminary or partial results, lack details needed for critical appraisal, and have not undergone rigorous peer review. [4][5][6][7][8] Thus, full-length publications in peer-reviewed journals are commonly considered the expected outcome of conference presentations and endpoint of high-quality research. [1,9,10] In publication fate studies, full publication rate (FPR), the proportion of abstracts presented at certain conferences that have resulted in full publication, and its predictors have been widely used as indicators of the quality of conferences and presented research, as well as measures of potential publication bias.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors that have been shown to increase the likelihood of abstract publication include: oral presentation (as opposed to a poster), statistical analysis, number of authors, and university affiliation. [28][29][30][31] Time to publication is generally about 20 months. 29 …”
Section: After the Presentationmentioning
confidence: 99%
“…1 Their results showed that, of 239 abstracts presented either as oral or poster presentations, 64 (27%) were ultimately published as full-length manuscripts in peer-reviewed journals.…”
mentioning
confidence: 99%